2020
DOI: 10.24331/ijere.646832
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Classroom Management Skills of Teachers Leads to Creating Positive Classroom Climate

Abstract: This study aims to evaluate the effects of "Classroom Management Training Programme" on preschool teachers' teaching styles regarding classroom management practices and children's behaviors in the classroom atmosphere. For this study, thirty teachers were selected from the schools in İzmir by convenience sampling method. In this quasi-experimental study with a pre-testintervention-post-test design, data was collected thorough Teaching Style Rating Scale (TSRS), Classroom Atmosphere Rating Scale (CARS) and Semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a study conducted in the United States (Wright et al, 2017), researchers found that similarities in cultural practices and expectations (including both children and teachers) would help to reduce externalizing behavior problems of children within communication. On the other hand, given their responsible adult role, teacher's positive, encouraging, and supportive relationship style as well as proactive behavior management strategies would contribute more to strengthen child-teacher and child-child relationships (Emmer & Stough, 2001;Greenberg et al, 2018;Güzeldere Aydın & Ocak Karabay, 2020). Research has also focused on how student-centered learning practices reduce misbehaviors and promote supportive, respectful relationships, compared to teacher-dominated classroom environments (Freiberg, 2006;Garrett, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the United States (Wright et al, 2017), researchers found that similarities in cultural practices and expectations (including both children and teachers) would help to reduce externalizing behavior problems of children within communication. On the other hand, given their responsible adult role, teacher's positive, encouraging, and supportive relationship style as well as proactive behavior management strategies would contribute more to strengthen child-teacher and child-child relationships (Emmer & Stough, 2001;Greenberg et al, 2018;Güzeldere Aydın & Ocak Karabay, 2020). Research has also focused on how student-centered learning practices reduce misbehaviors and promote supportive, respectful relationships, compared to teacher-dominated classroom environments (Freiberg, 2006;Garrett, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When the literature is examined, it is seen that there are studies investigating the teachers' classroom management styles (Adedigba & Sulaiman, 2020;Barrosa & Dias, 2020;Berger & Girardet, 2020;Debbag & Fidan, 2020;Guzeldere Aydin & Ocak Karabay, 2020;Juta & Wyk, 2020;Obiekwe & Ogbo, 2020) and communication skills (Claro, et al, 2018;Ihmeideh, Al-Omari & Al-Dababneh, 2010;Siddiq, Scherer & Tondeur, 2016;Yesil, 2010;Yusof & Halim, 2014), however we have not found any study which investigate the impact of teachers communication skills, together with gender, professional seniority and school stage, on their classroom management styles. In this context, this study aimed to fill this gap and to test the impacts of communication skills, professional seniority, school stages and gender as predictors of teachers' classroom management styles.…”
Section: Introductionmentioning
confidence: 89%
“…Junior high school students still do the memorizing habit as in their elementary school because the interaction of students with their teacher will leave permanent traces (Aydin & Karabay, 2020). Despite the variety of learning models introduced, most teachers tend to apply traditional learning which only functions the small brain.…”
Section: Introductionmentioning
confidence: 99%